Physical Layer Approaches for Securing Wireless Communication Systems - Wen, Hong (SpringerBriefs in Computer Science, 2013)
This book surveys the outstanding work of physical-layer (PHY) security, including  the recent achievements of confidentiality and authentication for wireless communication systems by channel identification. A practical approach to building unconditional confidentiality for Wireless Communication security by feedback and error correcting code is introduced and a framework of PHY security based on space time block code (STBC) MIMO system is demonstrated.  Also discussed is a scheme which combines cryptographic techniques implemented in the higher layer with the physical layer security approach using redundant antennas of MIMO systems to provide stronger security for wireless networks. The channel responses between communication peers have been explored as a form of fingerprint with spatial and temporal uniqueness. Finally, the book develops a new lightweight method of channel identification for Sybil attack and node clone detection in wireless sensor networks (WSNs).